Application of next-generation sequencing in the detection of transgenic crop - He, Shitian; Fan, Yueyuan; Tao, Shaomin; Zhang, Yanxia; Yin, Chuanlin; Yu, Xiaoping (Frontiers in Genetics, 2024)
With the rapid development of transgenic technology and the increasing prevalence of genetically modified (GMO) crops, incidents such as illegal importation, environmental contamination, and safety concerns associated with GMOs have risen significantly in recent years. Consequently, there is a growing demand for more advanced methods of GMO crop detection. Traditional molecular detection techniques, which rely on nucleic acids or proteins, are becoming less effective due to the increasing complexity of GMO crop genomes. In contrast, detection technologies based on second- and third-generation high-throughput sequencing offer promising solutions to these challenges. This review provides a comprehensive overview of the latest advancements in GMO crop detection technologies, categorizing and describing various approaches, and comparing their respective strengths and limitations. The article emphasizes the current state, benefits, challenges, and future prospects of high-throughput sequencing in GMO detection, aiming to guide further research and development in this field.